Towards e-health: Information technologies for increasing entrepreneurship - Aelita Skarézauskiençe; Rasa Juciute-Rotomskiençe (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Today`s organizations are increasingly finding themselves in a world characterized by globalization, turbulence and complexity, paralleled with an exponential advancement in information technology (IT). These conditions require flexibility, collaboration, innovation and the courage to embrace uncertainty and ambiguity. Such extreme challenges require radical solutions and the transformation of organization development. Improving efficiency and effectiveness in knowledge-intensive society demands sophisticated technologies - learn from and solve problems with other people in organisations using new technologies. Social technologies are powerful tool for holding organizations accountable for their social impact. Information technology has experienced many cycles of innovation, producing always more complex and integrated set of technologies to respond directly to society needs. The paper presents new management practices using social technologies in public administration organizations for addressing higher costumer expectations. Drawing on quantitative evidences the paper is seeking to improve our understanding of the role of information technologies and to give guidance on how to handle the relationship between technologies and entrepreneurship in public administration organisations with special attention to health sector.
Keywords: 650; e-Health; information technologies; social technologies; knowledge management; innovation; entrepreneurship